Elements of patriotism in "Pahlawan Pasir Salak" novel - Aziz, Maizatul Akma; Nik Mohamad Affendi, Nik Rafidah; Mohd Hanafiah, Halis Azhan; Kamarudin, Kamariah (Human Resource Management Academic Research Society, 2017)
This study focuses on the elements of patriotism in the novel "Pahlawan Pasir Salak" by Mohd Ismail Sarbini. This novel is a compulsory Bahasa Melayu text used as a Literature Component for Form Two. The setting of this novel is during the British Colonial Era. There are seven elements of patriotism adopted as the basis for the study which are Personal Patriotism, Official Patriotism, Icon Patriotism, Symbolic Patriotism, Capital Patriotism, Environment Patriotism and Symbolic Nationalists Patriotism. According to the study, the personal, icons, symbolic nationalist as well as capital patriotism is found to be very dorminant through the characters and certain events occurring in this novel. These patriotism elements are very important to be instilled in the next generation of our country that is emerging in the golden era for the betterment of the nation.